On Cooling the Tourist Out Notes on the Management of Spoiled Expectations - Nutch, Frank (Qualitative Sociology Review, 2007)
This article focuses on the social world of the commercial whale watch cruise. It draws on several years of participant observation research with marine field scientists, particularly field scientists who serve as naturalists on commercial whale watch cruises. Using Erving Goffman’s work, the essay details how the naturalist’s narration is an example of “cooling the mark out” that Goffman conceptually outlined and others have explored. In the social world of the commercial whale watch, the naturalist is the “operator and the tourist the mark”. It is argued that the naturalist’s narration is the principal means for cooling the tourists’ out. This is done within a context of the operator anticipating a set of spoiled expectations the tourist is likely to experience. While this essay extends the work of Goffman and others who have explored different settings of the cooling out process, it substantially differs from them. Past studies have focused on the cooling out process primarily within a context of individual face-to-face interaction. This essay looks at the commercial whale watch as a social setting of cooling out the mark not on a face-to-face basis but as a process of a “group of individuals who are being “cooled”. Most importantly, this is viewed as occurring not after they have been conned or duped but in anticipation of their likely experiencing a set of spoiled expectations.